A Briquette Characteristics of Cocoa Shell Charcoal and Rice Husk Charcoal Mixtures on Briquette Quality : Karakteristik Briket Campuran Arang Kulit Kakao dan Arang Sekam Padi Terhadap Mutu Briket - Aulia, Yuliatin; Muliatiningsih; Karyanik; Muanah; Ahmad Akromul Huda (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2024)
Biomass energy is produced by converting solid raw materials into a more useful compressed form known as briquettes. This study aims to examine the effect of varying compositions of charcoal briquettes using a mixture of cocoa shells and rice husks on the briquette characteristics. The experimental method employs a Completely Randomized Design with four treatments: P1 = 100% cocoa shells, P2 = 75% cocoa shells + 25% rice husks, P3 = 25% cocoa shells + 75% rice husks, and P4 = 100% rice husks. The study finds that the lowest moisture content is in P3 (8.01%), the lowest ash content is in P3 and P4 (4.1% and 3.8%, respectively), the highest calorific value is in P1 (3,658 cal/g), the longest ignition time is in P3 (50 minutes), and the best hardness is in P2 (785.95 N). Based on the results, the best treatment is P3, which achieves a moisture content of 8.01%, ash content of 4.1%, and the longest burning time of 50 minutes.